Five-Year Survival with Combined Nivolumab and Ipilimumab in Advanced Melanoma - John Wagstaff (New England Journal of Medicine, 2019)
945 patients with inoperable stage III or stage IV melanoma were randomised to ipilimumab plus nivolumab (ipi/nivo)(314), nivolumab (nivo) (316) or ipilimumab (Ipilimumab) (315). The minimum follow up from randomisation of the last patient was 60 months. Objective responses were seen in 58% of Ipilimumab/nivo, 45% of nivo and 19% of Ipilimumab patients. Complete responses were seen in 22% (Ipilimumab/nivo), 19% (nivo) and 6% (Ipi) patients. Overall survival (OS) at five years was 52% (Ipilimumab/nivo), 44% (nivo) and 26% (Ipi). In patients with and without bras mutations the OS at five years was 60 & 48% (Ipilimumab/nivo), 46 & 43% (nivo) and 30 & 25% (Ipi) respectively. OS curves were flat beyond three years indicating that these treatments lead to sustained long term survival of these patients.